2020
DOI: 10.1111/cei.13546
|View full text |Cite
|
Sign up to set email alerts
|

Roles of cytokines and T cells in the pathogenesis of myasthenia gravis

Abstract: Activated T cells, B cells, plasma cells, and related cytokines play central roles in the production of pathogenic autoantibodies in myasthenia gravis (MG). T helper 17 (Th17) cells, follicular Th (Tfh) cells, and related cytokines are upregulated, whereas regulatory T (Treg) cells and related cytokines are downregulated. Chronic inflammation by Th17 cells, the promotion of autoantibody production from B cells and plasma cells by Tfh cells or B‐cell‐related cytokines, and the activation of the immune response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 74 publications
0
59
0
Order By: Relevance
“…Multiple mechanisms are implicated, including the release of interleukin 17 (IL-17), among other cytokines, which indirectly promote immunoglobulin production. Th17 cells also affect the balance of the cytokine profile of Th1 and Th2 cells, thus influencing antibody production [ 118 ]. Several studies have shown that patients with MG have elevated levels of Th17 cells and IL-17, which correlate with disease severity and antibody titers [ 119 , 120 ].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Multiple mechanisms are implicated, including the release of interleukin 17 (IL-17), among other cytokines, which indirectly promote immunoglobulin production. Th17 cells also affect the balance of the cytokine profile of Th1 and Th2 cells, thus influencing antibody production [ 118 ]. Several studies have shown that patients with MG have elevated levels of Th17 cells and IL-17, which correlate with disease severity and antibody titers [ 119 , 120 ].…”
Section: Pathophysiologymentioning
confidence: 99%
“…The immune system is a critical regulator of both neurological ( Prinz and Priller, 2017 ) and muscular ( Farup et al, 2015 ) homeostasis, injury response, and pathology. The chronic injury cycles characteristic of multiple NMDs result in persistent and increased infiltration of monocytes/macrophages ( Acharyya et al, 2007 ), T lymphocytes ( Uzawa et al, 2021 ), and mast cells ( Trias et al, 2017 ) at NMJs. These cells secrete multiple factors that induce a chronic pro-inflammatory environment and contribute to disease progression through several mechanisms that increase oxidative stress and alter stem cell function.…”
Section: Discussionmentioning
confidence: 99%
“…Although the actual underlying mechanisms of MG are unclear, presence of ectopic germinal centers (GCs) and loss of central as well as peripheral tolerance have been discussed (1). High numbers of Th17 cells, follicular Th (Tfh) cells, and dysfunction of Tregs have been shown to promote autoantibody production from B cells and plasma cells (PCs), thereby exacerbating MG pathogenesis (45). Interestingly, the pattern of MG pathogenesis, to some extent, overlaps with the underlying mechanism of vaccine action.…”
Section: Mechanism Of Vaccination and Mgmentioning
confidence: 99%
“…Interestingly, the pattern of MG pathogenesis, to some extent, overlaps with the underlying mechanism of vaccine action. For example, Tfh cells are required for GCs, Abs, and long-lived PC responses, not only in MG but also in vaccine immunization (45,46). Nonetheless, the link between the underlying mechanism of vaccination action and MG remains unclear.…”
Section: Mechanism Of Vaccination and Mgmentioning
confidence: 99%